Motion-Genetic Testing is Useful in the Diagnosis of Nonhereditary Pancreatic Conditions: Arguments for the Motion - David C Whitcomb (Canadian Journal of Gastroenterology)
Mutations of three major genes are associated with an increased risk of acute and chronic pancreatitis: the cationic trypsinogen (PRSS1) gene, the cystic fibrosis transmembrane conductance regulator (CFTR) gene, and the pancreatic secretory trypsin inhibitor (PSTI) or serine protease inhibitor, Kazal type 1 (SPINK1) gene. Some autosomal dominant forms of hereditary pancreatitis are associated with mutations of the PRSS1 gene, which can be readily identified by genetic testing. Mutations of the CFTR gene can lead either to cystic fibrosis or to idiopathic chronic pancreatitis, and to a variety of cystic fibrosis-associated disorders, including congenital bilateral absence of the vas deferens and sinusitis. These mutations, as with those of the SPINK1 (or PSTI) gene, are prevalent in North America; thus, the presence of such a mutation in an asymptomatic person does not confer a high risk of developing pancreatitis. Combinations of mutations of the PRSS1 and SPINK1 genes lead to more severe disease, as indicated by an earlier onset of symptoms, which suggests that SPINK1 is a disease modifier. The major fear expressed by potential candidates for genetic testing is that the results could lead to insurance discrimination. Studies of the positive predictive value of genetic tests are hampered by recruitment bias and lack of knowledge of family history of pancreatitis. Genetic testing is most useful for persons for whom family members have already been found to exhibit a particular pancreatitis-associated mutation. In the future, increased knowledge of the myriad genetic causes of pancreatitis, as well as advances in the diagnosis and treatment of early chronic pancreatitis, should enhance the utility of genetic testing.